2020
DOI: 10.1111/jcpe.13278
|View full text |Cite
|
Sign up to set email alerts
|

The effect of transcrestal sinus‐floor elevation without graft on the long‐term prognosis of maxillary implants

Abstract: Aim To evaluate the effects of (a) transcrestal sinus‐floor elevation (TSFE) and (b) residual bone height on long‐term implant survival. Materials and Methods Chi‐squared and t tests were used for descriptive comparison of the groups. Kaplan–Meier survival curves and corresponding log‐rank tests were used to investigate implant survival over time. Multivariable Cox regressions were performed for the total population and experimental group. Results A total of 634 patients received 648 implants with TSFE, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 34 publications
2
21
0
3
Order By: Relevance
“…Em nosso estudo, um valor comparável foi calculado para ganho ósseo apical após um período de observação de 4 anos. Uma revisão diferente [ 17 ], no entanto, relatou variação no ganho ósseo vertical entre 1,7 mm e 4,1 mm em grupos sem enxerto após 3 anos. Com base nos achados do nosso estudo, a variação no ganho ósseo vertical foi predominantemente afetada pela quantidade de altura óssea residual.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Em nosso estudo, um valor comparável foi calculado para ganho ósseo apical após um período de observação de 4 anos. Uma revisão diferente [ 17 ], no entanto, relatou variação no ganho ósseo vertical entre 1,7 mm e 4,1 mm em grupos sem enxerto após 3 anos. Com base nos achados do nosso estudo, a variação no ganho ósseo vertical foi predominantemente afetada pela quantidade de altura óssea residual.…”
Section: Discussionunclassified
“…No entanto, aqui o período de observação foi bastante curto, com 17 meses de acompanhamento. Com relação ao prognóstico do implante, os autores deste estudo também relataram que alturas ósseas residuais inferiores a 4 mm e perfurações na membrana reduzem a probabilidade de sobrevida em 10 anos [ 17 ].…”
Section: Introductionunclassified
“…The surgical procedures are also described in previous works [ 16 , 17 ]. After local anesthesia, mid-crestal incision was performed and buccal / palatal full-thickness flaps were reflected.…”
Section: Methodsmentioning
confidence: 99%
“…However, here the observation period was rather short with 17-months follow-up. With regard to implant prognosis, the authors of this study also reported that residual bone heights lower than 4 mm and membrane perforations reduce the probability of 10-year survival [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies point to long-term (over 10 years) predictability of OSFE without grafting (Caban et al, 2017;Fugazzotto, 2017;Nedir et al, 2016;Rammelsberg et al, 2020). In a retrospective study, 22 implants have been followed for 10 years.…”
Section: Introductionmentioning
confidence: 99%